Adhesive for corrugated paper and preparation method thereof
By using adhesives prepared by raw materials such as polycaprolactone diol, toluene diisocyanate, etc., a dense network structure is formed through crosslinking and cassava flour filling, the problem of insufficient viscosity and bonding strength of existing pit paper adhesives is solved, and higher adhesive strength and durability are achieved.
Patent Information
- Application Number
- CN202310217773.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-03-08
AI Technical Summary
The viscosity and bond strength of existing adhesives for pit paper are low, making it difficult to meet the high-efficiency adhesive requirements for pit paper.
The raw materials such as polycaprolactone diol, toluene diisocyanate, crosslinking agent, chain extender, epoxy resin, cassava flour and polymerization liquid are used to form a dense interpenetrating network structure through mixing reaction and crosslinking, and the adhesive bonding performance of the adhesive is improved through the filling of cassava flour.
It significantly improves the adhesive strength, low temperature resistance, flexibility and aging resistance, making it more suitable for adhesive applications of pit paper.
Smart Images

Figure BDA0004115541420000071 
Figure BDA0004115541420000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of an adhesive for corrugated paper, and in particular to an adhesive for corrugated paper and a preparation method thereof. Background Art
[0002] With the continuous development of society, the requirements for packaging materials are also increasing. The packaging performance of packaging materials needs to be continuously improved to meet the packaging needs of different objects. Therefore, the packaging performance of packaging materials also needs to continue to improve and develop; among them, corrugated paper, as a type of packaging paper, is one of the important materials in paper packaging. The fundamental structure of corrugated paper is a smooth kraft paper and a wavy paper (collectively referred to as paper core) laminated together. It has good supporting properties and is therefore suitable for preparing packaging materials. When corrugated paper is used to prepare packaging materials, it is necessary to glue the corrugated paper with an adhesive to prepare cardboard, which is then folded and cut into packaging boxes. At present, many adhesives on the market mainly use starch as the raw material for preparing the adhesive. Starch is naturally renewable, environmentally friendly, non-toxic, and easily biodegradable, and is therefore widely used.
[0003] In the above-mentioned related technologies, the inventors believe that the starch adhesive prepared with starch as the main material in the prior art has the problems of low viscosity and low bonding strength when gluing corrugated paper, so the bonding strength of the existing corrugated paper adhesive needs to be improved. Summary of the invention
[0004] In order to improve the adhesive strength of the adhesive to the corrugated paper, the present application provides an adhesive for corrugated paper and a preparation method thereof.
[0005] In the first aspect, the present application provides an adhesive for corrugated paper, which adopts the following technical solution:
[0006] An adhesive for corrugated paper mainly comprises the following raw materials in parts by weight: 30-60 parts of polycaprolactone diol, 15-25 parts of toluene diisocyanate, 3-8 parts of a cross-linking agent, 5-10 parts of a chain extender, 2-3 parts of dibutyltin dilaurate, 5-10 parts of cassava flour, 3-5 parts of a polymer solution, and 10-15 parts of an epoxy resin; the polymer solution comprises azobisisobutyronitrile.
[0007] By adopting the above technical scheme, polycaprolactone diol and toluene diisocyanate are mixed and reacted to make the isocyanate group and the polyol mixed. Under the crosslinking action of the crosslinking agent, the isocyanate group and the polyol are crosslinked to form a polyurethane molecule. The soft segment and the hard segment in the polyurethane molecular chain structure are staggered, so that the prepared adhesive has the characteristics of low temperature resistance, good flexibility, strong adhesion, good aging resistance, etc., and can be used for the bonding of corrugated paper; by adding epoxy resin to the raw materials for preparing the adhesive, in the preparation process of the adhesive, the epoxy resin is completely ring-opened, and the ring-opened epoxy resin and the polyol are cross-linked under the action of the chain extender. The urethane undergoes cross-linking to generate an interpenetrating network structure, making the internal structure of the adhesive more compact and stable; cassava flour is environmentally friendly and odorless. The main component of cassava flour is cassava starch, which is rich in amylopectin and straight-chain starch, so it has a very high viscosity. After being added to the adhesive mainly composed of polyurethane, the network structure is filled, which can effectively improve the bonding properties of the prepared adhesive, so that the prepared adhesive has better bonding strength to the corrugated paper; the chain extender used in this application is 1.4-butanediol; the polymerization liquid used in this application is a mixture of azobisisobutyronitrile and acetone in a mass ratio of 3:8.
[0008] Optionally, the cassava flour is modified before use: cassava flour, glycerol and p-toluenesulfonic acid are mixed together to prepare a mixture, the mixture is stirred at a pressure of 0.05-0.1 MPa and a temperature of 100-120° C., and cooled to obtain a pre-reactant; anhydrous sodium carbonate is added to adjust the pre-reactant to neutrality, and decompressed and dehydrated to obtain the pre-reactant; the mass ratio of cassava flour, glycerol and p-toluenesulfonic acid is (3-5):(5-7):(0.4-0.6).
[0009] By adopting the above technical scheme, cassava flour can be degraded and regenerated and has good viscosity. The cassava flour is mixed with glycerol and p-toluenesulfonic acid for reaction, the cassava flour is refined and liquefied, and the cassava flour is modified to prepare modified cassava flour, so that the modified cassava flour has a larger contact area and reaction site with other raw materials in the adhesive, thereby enhancing the filling effect of the modified cassava flour network structure and the improvement effect on the adhesive properties of the adhesive.
[0010] Optionally, the crosslinking agent is composed of trihydroxymethylpropane and epoxysilane in a mass ratio of (1-3):(2-3).
[0011] By adopting the above technical scheme, trihydroxymethylpropane is used as a cross-linking agent to promote the cross-linking and curing of polyurethane, so that the adhesive prepared after the cross-linking of polyurethane has good adhesive strength and heat resistance; one end of the epoxy silane molecular chain is an epoxy group, and the other end is an alkoxy silane group. The epoxy group of epoxy silane can react with the amine group and the carboxyl group in the polyurethane at the same time to promote the curing of the polyurethane, and the alkoxy silane group can improve the strength of the adhesive; by compounding trihydroxymethylpropane and epoxy silane, the preparation of the adhesive is promoted and the adhesive strength of the prepared adhesive is improved.
[0012] In a second aspect, the present application provides a method for preparing an adhesive for corrugated paper;
[0013] A method for preparing an adhesive for corrugated paper mainly comprises the following steps:
[0014] S1: After mixing polycaprolactone diol, toluene diisocyanate and a crosslinking agent, reacting at 70-80° C. for 1-2 hours to obtain a prepolymer;
[0015] S2: adding a chain extender, an epoxy resin and dibutyltin dilaurate to the prepolymer prepared in step S1, and heat-retaining the reaction for 3-5 hours to obtain a pre-reactant;
[0016] S3: After the pre-reactant prepared in step S2 is quickly stirred, cassava flour and polymer solution are added to the pre-reactant, reacted at 60-80° C. for 2-4 hours, and cooled to obtain the product.
[0017] By adopting the above technical scheme, polycaprolactone diol, toluene diisocyanate and a cross-linking agent are first mixed and reacted together. Under the action of the cross-linking agent, the isocyanate groups on the polycaprolactone diol and toluene diisocyanate and the polyol undergo a cross-linking reaction to form polyurethane molecules. Then, a chain extender, an epoxy resin and dibutyl tin dilaurate are added to allow the epoxy resin to undergo a ring-opening reaction and cross-link with the polyurethane molecules to form a dense cross-linked interpenetrating network structure. Subsequently, cassava flour and a polymer solution are added to fill the interpenetrating network structure with cassava flour to improve the density of the adhesive. At the same time, the polymer solution promotes the emulsification polymerization of the adhesive to further improve the density and mechanical strength of the internal structure of the adhesive, so that the generated adhesive is more stable and has better bonding strength to the corrugated paper.
[0018] Optionally, before the pre-reactant is rapidly stirred in step S3, methyl methacrylate and hydroxyethyl acrylate are added to the pre-reactant.
[0019] By adopting the above technical scheme, methyl methacrylate and hydroxyethyl acrylate are added, and in the preparation process of the adhesive, methyl methacrylate and hydroxyethyl acrylate are polymerized and cross-linked to generate methyl methacrylate monomer, and the methyl methacrylate monomer is emulsion polymerized with the polyurethane. At the same time, after the epoxy resin is ring-opened in the preparation process of the adhesive, the ring-opened epoxy resin and the methyl methacrylate monomer are jointly connected to the polyurethane molecular chain, the polyurethane is modified, and an emulsion with a core-shell cross-linked structure is generated, thereby improving the adhesive strength of the prepared adhesive.
[0020] Optionally, the mass ratio of the epoxy resin, methyl methacrylate and hydroxyethyl acrylate is (3-5):(2-3):(1-2).
[0021] By adopting the above technical scheme, the epoxy resin is a polyhydroxy compound. When the epoxy resin reacts with the polyurethane, the branching point can be introduced into the main chain of the polyurethane, so that the network structure formed by the cross-linking of the epoxy resin and the polyurethane is more excellent. At the same time, the addition of the epoxy resin increases the tensile strength of the prepared adhesive, increases the cross-linking density in the adhesive, and increases the adhesive strength of the adhesive; the epoxy resin is combined with the methyl methacrylate monomer formed by methyl methacrylate and hydroxyethyl acrylate to form a core-shell structure, which further improves the adhesive strength of the prepared adhesive; the mass ratio of the epoxy resin, methyl methacrylate and hydroxyethyl acrylate is adjusted. When the amount of epoxy resin added is too much, precipitation is likely to occur during the preparation of the adhesive, which reduces the stability and adhesive strength of the prepared adhesive; when the amount of epoxy resin added is too little, the adhesive strength of the prepared adhesive is insufficient, which affects the adhesive performance to the corrugated paper.
[0022] Optionally, in step S3, after adding the epoxy resin and dibutyltin dilaurate to the reaction bottle, 7-13 parts of a filler are also added to the reaction bottle; the filler is composed of montmorillonite and attapulgite in a mass ratio of (3-5):(2-4).
[0023] By adopting the above technical scheme, since montmorillonite is a mineral with a layered silicate structure, its crystals are lamellar structures and have permanent negative charges on the surface, and have good adsorption properties; attapulgite is a hydrated magnesium-rich aluminum silicate clay mineral with a chain layered structure, and its crystals are needle-rod shaped. After the attapulgite is dispersed, since the end faces of the crystals are positively charged and the sides are negatively charged, there is an electrostatic effect between the two. Under the action of hydrogen bonds, montmorillonite platelets and attapulgite rod crystals can form a composite structure, which supports the adhesive and makes the prepared adhesive have better bonding strength.
[0024] Optionally, the filler is pretreated before use to prepare a pretreated filler, and the pretreatment comprises the following steps: crushing the filler, immersing it in an acid solution with a pH value of 2-4, and preparing a mixture after mixing evenly; slowly adding sodium hydroxide solution to the mixture, adjusting the pH value of the mixture to 11-13, filtering, and drying.
[0025] By adopting the above technical scheme, the filler is first immersed in acid solution, and through the hydration and erosion of the acid solution, the lamellar crystal structure of montmorillonite is easy to be peeled off, and the rod crystal structure of attapulgite is also easy to be separated, and a large number of rod crystal structures are subsequently formed. With the addition of sodium hydroxide solution, the montmorillonite is gradually peeled off into a single-piece structure, and the fiber bundles of attapulgite are also dissociated to form a rod crystal structure. Then, the rod crystal structure of attapulgite and the lamellar crystal structure of montmorillonite jointly form a "card room" structure, which plays a role of force support in the adhesive and improves the bonding strength of the adhesive to the corrugated paper.
[0026] Optionally, during the process of slowly adding the sodium hydroxide solution to the mixture, the mixture is subjected to ultrasonic treatment.
[0027] By adopting the above technical scheme, ultrasonic treatment accelerates the separation of montmorillonite lamellar crystal structure and attapulgite rod crystal structure, further accelerating the formation of "card room type" structure, so that the pretreated filler is added to the adhesive, which can more significantly improve the adhesive strength of the adhesive.
[0028] In summary, this application has the following beneficial effects:
[0029] The present application prepares a polyurethane adhesive by mixing polycaprolactone diol and toluene diisocyanate, generating polyurethane molecules under the action of a cross-linking agent, and polymerizing the polyurethane molecules with the ring-opened epoxy resin under heating reaction conditions through the action of a chain extender, so that the generated adhesive has a dense interpenetrating network structure, and the filling effect of cassava flour makes the prepared adhesive have strong adhesive properties, thereby making the prepared adhesive have a good adhesive effect on corrugated paper. DETAILED DESCRIPTION
[0030] The present application is further described in detail below with reference to the embodiments and comparative examples;
[0031] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0032] The epoxy resin used in the present application is composed of bisphenol A epoxy resin and glycidyl ester epoxy resin in a mass ratio of 2:1.
[0033] Preparation Example
[0034] Modified cassava flour preparation example 1
[0035] The preparation method of modified cassava flour in this preparation example comprises the following steps:
[0036] Take a mixing barrel, add cassava flour, glycerol and p-toluenesulfonic acid into the mixing barrel, mix well to prepare a mixture, seal and stir the mixture at 0.08 MPa and 110° C. for 2 hours, and obtain a pre-reactant after cooling, and then slowly add anhydrous sodium carbonate to the pre-reactant to adjust the pre-reactant to neutrality, and then decompress and dehydrate the pre-reactant at 100° C. for 1 hour to obtain the product; the mass ratio of cassava flour, glycerol and p-toluenesulfonic acid used is 3:5:0.4.
[0037] Modified cassava flour preparation example 2
[0038] The difference between the preparation method of modified cassava flour in this preparation example and that in the modified cassava flour preparation example 1 is that the mass ratio of cassava flour, glycerol and p-toluenesulfonic acid used is 5:7:0.6.
[0039] Modified cassava flour preparation example 3
[0040] The difference between the preparation method of modified cassava flour in this preparation example and that in the modified cassava flour preparation example 1 is that the mass ratio of cassava flour, glycerol and p-toluenesulfonic acid used is 4:6:0.5.
[0041] Example
[0042] Example 1
[0043] The raw materials for preparing the adhesive for corrugated paper in this embodiment mainly include: 30kg of polycaprolactone diol, 15kg of toluene diisocyanate, 3kg of cross-linking agent, 5kg of chain extender, 2kg of dibutyltin dilaurate, 5kg of cassava flour, 3kg of polymer solution, and 10kg of epoxy resin; the cross-linking agent used is composed of trihydroxymethylpropane and epoxysilane in a mass ratio of 1:3;
[0044] The preparation method of the adhesive for corrugated paper in this embodiment mainly comprises the following steps:
[0045] S1: Take a reaction bottle, add the above-mentioned weight proportions of polycaprolactone diol, toluene diisocyanate and cross-linking agent into the reaction bottle, stir evenly, heat the reaction bottle to 75° C. and react for 1.5 hours to obtain a prepolymer;
[0046] S2: Add the above-mentioned weight proportions of chain extender, epoxy resin and dibutyltin dilaurate to the prepolymer prepared in step S1, stir evenly, and then keep the reaction bottle at 70°C for 4 hours to obtain a pre-reactant; the chain extender used is 1.4-butanediol; S3: After stirring the pre-reactant prepared in step S2 at a speed of 150r / min for 10 minutes, add the above-mentioned weight proportions of cassava flour and polymerization liquid to the pre-reactant, and react at 70°C for 3 hours to obtain; the polymerization liquid used is a mixture of azobisisobutyronitrile and acetone in a mass ratio of 3:8.
[0047] Example 2
[0048] The preparation method of the adhesive for corrugated paper in this embodiment is different from that in Example 1 in that the raw materials for preparing the adhesive for corrugated paper mainly include: 60 kg of polycaprolactone diol, 25 kg of toluene diisocyanate, 8 kg of cross-linking agent, 10 kg of chain extender, 3 kg of dibutyl tin dilaurate, 10 kg of cassava flour, 5 kg of polymer liquid, and 15 kg of epoxy resin.
[0049] Example 3
[0050] The preparation method of the adhesive for corrugated paper in this embodiment is different from that in Example 1 in that the raw materials for preparing the adhesive for corrugated paper mainly include: 45 kg of polycaprolactone diol, 20 kg of toluene diisocyanate, 5 kg of cross-linking agent, 7 kg of chain extender, 2.5 kg of dibutyl tin dilaurate, 8 kg of cassava flour, 4 kg of polymer liquid, and 12 kg of epoxy resin.
[0051] Example 4
[0052] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Embodiment 3 in that the cross-linking agent in step S1 is composed of trihydroxymethylpropane and epoxysilane in a mass ratio of 3:2.
[0053] Example 5
[0054] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Embodiment 3 in that the cross-linking agent in step S1 is composed of trihydroxymethylpropane and epoxysilane in a mass ratio of 2:2.5.
[0055] Example 6
[0056] The preparation method of the adhesive for corrugated paper in this embodiment is different from that in Example 5 in that, after the chain extender, epoxy resin and dibutyl tin dilaurate are added to the reaction bottle in step S2, 10 kg of filler is also added to the reaction bottle, and the filler used is composed of montmorillonite and attapulgite in a mass ratio of 3:4; the filler used is pretreated before use, and the pretreatment includes the following steps: taking an immersion barrel, placing an acid solution with a pH value of 3 in the immersion barrel, crushing the filler and immersing it in the acid solution with a pH value of 3, mixing evenly to prepare a mixture; then slowly adding sodium hydroxide solution to the mixture, adjusting the pH value of the mixture to 12, and then filtering the mixture, washing and drying; the acid solution used is hydrochloric acid solution.
[0057] Example 7
[0058] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Embodiment 6 in that the filler used in step S2 is composed of montmorillonite and attapulgite in a mass ratio of 5:2.
[0059] Example 8
[0060] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Embodiment 6 in that the filler used in step S2 is composed of montmorillonite and attapulgite in a mass ratio of 4:3.
[0061] Example 9
[0062] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Embodiment 8 in that, when the filler is pretreated, the sodium hydroxide solution is slowly added to the mixture and the mixture is ultrasonically treated for 20 minutes.
[0063] Example 10
[0064] The preparation method of the adhesive for corrugated paper in this embodiment is different from that in Embodiment 9 in that, before the pre-reactant is stirred at 150 r / min in step S3, methyl methacrylate and hydroxyethyl acrylate are added to the pre-reactant; the mass ratio of the epoxy resin, methyl methacrylate and hydroxyethyl acrylate used is 3:2:1.
[0065] Embodiment 11
[0066] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Embodiment 10 in that the mass ratio of the epoxy resin, methyl methacrylate and hydroxyethyl acrylate used in step S3 is 5:3:2.
[0067] Example 12
[0068] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Embodiment 10 in that the mass ratio of the epoxy resin, methyl methacrylate and hydroxyethyl acrylate used in step S3 is 4:2.5:1.5.
[0069] Embodiment 13
[0070] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Example 12 in that the cassava flour used in step S3 is modified cassava flour prepared in Modified Cassava Flour Preparation Example 1.
[0071] Embodiment 14
[0072] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Example 12 in that the cassava flour used in step S3 is modified cassava flour prepared in Modified Cassava Flour Preparation Example 2.
[0073] Embodiment 15
[0074] The method for preparing the adhesive for corrugated paper in this embodiment is different from that in Example 12 in that the cassava flour used in step S3 is modified cassava flour prepared in Modified Cassava Flour Preparation Example 3.
[0075] Comparative Example
[0076] Comparative Example 1
[0077] The preparation method of the adhesive for corrugated paper in this comparative example is different from that in Example 1 in that the raw materials used for the adhesive for corrugated paper do not contain epoxy resin.
[0078] Comparative Example 2
[0079] The preparation method of the adhesive for corrugated paper in this comparative example is different from that in Example 1 in that the raw materials used for the adhesive for corrugated paper do not contain cassava flour.
[0080] Detection Methods
[0081] According to the preparation method of the adhesive for corrugated paper in Example 1-15 and Comparative Example 1-2, an adhesive was prepared as an experimental sample, two corrugated papers of the same size were taken, and the adhesive was applied on the corrugated papers. The adhesive applied per square meter of corrugated paper was 50 g, and the two corrugated papers were bonded by the adhesive. After standing and drying for 24 hours, the object to be tested was prepared. Referring to the national standard GB / T2794-1995, the peel strength of the object to be tested was measured by using a WZL-300 horizontal computer tensile tester, and the data was recorded to obtain Table 1;
[0082] Table 1 Peel strength of the adhesive for corrugated paper prepared in Examples 1-15 and Comparative Examples 1-2
[0083]
[0084]
[0085] It can be seen from Examples 1-5, Comparative Examples 1-2 and Table 1 that by adding epoxy resin to the prepared adhesive, after polycaprolactone diol and toluene diisocyanate are cross-linked to generate polyurethane, the epoxy resin is ring-opened in the adhesive to cross-link with the polyurethane to generate a dense network structure, thereby improving the adhesive strength of the adhesive; by adjusting the mass ratio of trimethylolpropane and epoxysilane, when trimethylolpropane and epoxysilane are composed in a mass ratio of 2:2.5, trimethylolpropane promotes the cross-linking synthesis of polyurethane and also improves the heat resistance of the prepared adhesive, and in addition, the epoxy group of epoxysilane reacts with the amino group and carboxyl group in the polyurethane to promote the generation and curing of the polyurethane, thereby improving the adhesive strength of the prepared adhesive; and by comparing the data with Comparative Example 2, after adding cassava flour, the filling effect of cassava flour on the network structure makes the internal structure of the prepared adhesive more dense, and the adhesive properties of the adhesive are further improved by the adhesive properties of cassava flour itself.
[0086] Combining Examples 6-12 and Table 1, it can be seen that by adding a filler to the adhesive, adjusting the mass ratio of montmorillonite and attapulgite in the filler, and pre-treating the filler, the lamellar crystals of the montmorillonite are peeled off, and the crystal rods of the attapulgite are also peeled off, forming a "card room" structure to support the adhesive, and by ultrasonic treatment, the rate of formation of the "card room" structure is accelerated, and the adhesive strength of the adhesive is improved; and by adding methyl methacrylate and hydroxyethyl acrylate to the adhesive, methyl methacrylate and hydroxyethyl acrylate are cross-linked to generate methyl methacrylate monomer, and methyl methacrylate The methyl ester monomer and the polyurethane undergo emulsion polymerization, and the epoxy resin is connected to the polyurethane molecular chain together with the methyl methacrylate monomer after ring opening to generate a composite adhesive structure with a core-shell structure, thereby improving the adhesive properties of the adhesive. It can be seen from Examples 12-15 and Table 1 that by mixing cassava flour, glycerol and p-toluenesulfonic acid together, the cassava flour is pretreated so that the cassava flour is refined and liquefied, and the mass ratio of cassava flour, glycerol and p-toluenesulfonic acid is adjusted so that the prepared modified cassava flour has better contact and reaction sites with other raw materials in the adhesive, thereby improving the effect of the modified cassava flour on improving the adhesive strength of the adhesive.
[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An adhesive for corrugated paper, characterized in that: The method mainly comprises the following raw materials in parts by weight: 30-60 parts of polycaprolactone diol, 15-25 parts of toluene diisocyanate, 3-8 parts of a crosslinking agent, 5-10 parts of a chain extender, 2-3 parts of dibutyltin dilaurate, 5-10 parts of cassava flour, 3-5 parts of a polymerization liquid, and 10-15 parts of an epoxy resin; the polymerization liquid is prepared by mixing azobisisobutyronitrile and acetone in a mass ratio of 3:8; The cassava flour is modified before use: cassava flour, glycerol and p-toluenesulfonic acid are mixed together to prepare a mixture, the mixture is stirred at a pressure of 0.05-0.1 MPa and a temperature of 100-120° C., and cooled to obtain a pre-reactant; anhydrous sodium carbonate is added to adjust the pre-reactant to neutrality, and decompression and dehydration are performed to obtain the pre-reactant; the mass ratio of cassava flour, glycerol and p-toluenesulfonic acid is (3-5):(5-7):(0.4-0.6); The crosslinking agent is composed of trihydroxymethylpropane and epoxysilane in a mass ratio of (2-3):(2-2.5).
2. A method for preparing the adhesive for corrugated paper according to claim 1, characterized in that: The main steps are as follows: S1: After mixing polycaprolactone diol, toluene diisocyanate and a crosslinking agent, reacting at 70-80° C. for 1-2 hours to obtain a prepolymer; S2: adding a chain extender, an epoxy resin and dibutyltin dilaurate to the prepolymer prepared in step S1, and heat-retaining the reaction for 3-5 hours to obtain a pre-reactant; S3: After the pre-reactant prepared in step S2 is rapidly stirred, cassava flour and polymer solution are added to the pre-reactant, reacted at 60-80° C. for 2-4 hours, and cooled to obtain; In step S3, before the pre-reactant is rapidly stirred, methyl methacrylate and hydroxyethyl acrylate are added to the pre-reactant; The mass ratio of the epoxy resin, methyl methacrylate and hydroxyethyl acrylate is (3-5):(2-3):(1-2); In step S3, after the epoxy resin and dibutyltin dilaurate are added to the reaction bottle, 7-13 parts of a filler are added to the reaction bottle; the filler is composed of montmorillonite and attapulgite in a mass ratio of (3-5):(2-4); The filler is pretreated before use to prepare a pretreated filler, and the pretreatment comprises the following steps: crushing the filler, immersing it in an acid solution with a pH value of 2-4, and mixing it evenly to prepare a mixture; slowly adding a sodium hydroxide solution to the mixture, adjusting the pH value of the mixture to 11-13, filtering, and drying; The mixture is subjected to ultrasonic treatment while the sodium hydroxide solution is slowly added to the mixture.
Citation Information
Patent Citations
Preparing method for starch-based polyether polyol
CN105111430A
Water-proof and anti-corrosion floor adhesive
CN107858134A